My Enemy, My Neighbour: Characteristics and Challenges of Arabic Instruction in Israeli-Jewish Society. Issue 1 (May 2021) - Amara, Muhammad
Abstract : This article examines Arabic instruction in Israeli Hebrew schools with regard to the political, social, cultural, historical and pedagogical issues shaping it. It examines challenges facing Arabic instruction in Israel's education system, emphasising the dissonance between potential benefits of studying Arabic and its overall marginalised status in Israel. This article argues that that the main factors shaping Arabic instruction in Israeli-Jewish schools since 1948 are official security considerations and security claims — Arabic is studied as the language of the enemy and not the neighbour. A radical policy shift is required to 'civilianise' and demilitarise Arabic instruction and transform it into a bridge for understanding between Israeli-Jews, Palestinian-Arab citizens of Israel, in particular, the Palestinians, in general, as well as Israel's Arab neighbours in the Middle East.